2019
DOI: 10.1002/cjce.23399
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of nucleate pool boiling heat transfer of self‐rewetting solution by surface functionalization with TiO2 nanostructure

Abstract: A titanium plate with titanium dioxide nanotube was prepared with the anodic oxidation process. The heat transfer through this plate was studied with quantitative heptanol solution as self-rewetting solution. The microstructure of this nano-structure surface was characterized by SEM and the surface tension of the self-rewetting solution on it was measured by the static contact angle. The results indicated that the heat transfer coefficient (HTC) and the critical heat flux (CHF) were significantly improved with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Research on the pool boiling of SRFs on modified surfaces is scarce. Hu et al [59] investigated the boiling of mixtures of heptanol and water on flat titanium surfaces with titanium dioxide nanotubes prepared via anodic oxidation and reported significant enhancement of HTC and CHF. Zhou et al [60] experimented with the boiling of 1-butanol/water mixtures on a flat copper surface bonded with copper foam and achieved minor enhancement of heat transfer using their densest foam.…”
Section: Self-rewetting Fluidsmentioning
confidence: 99%
“…Research on the pool boiling of SRFs on modified surfaces is scarce. Hu et al [59] investigated the boiling of mixtures of heptanol and water on flat titanium surfaces with titanium dioxide nanotubes prepared via anodic oxidation and reported significant enhancement of HTC and CHF. Zhou et al [60] experimented with the boiling of 1-butanol/water mixtures on a flat copper surface bonded with copper foam and achieved minor enhancement of heat transfer using their densest foam.…”
Section: Self-rewetting Fluidsmentioning
confidence: 99%
“…For instance, Ohta [41] discusses reduced CHF for mixtures of water and alcohols and concludes that, as the Marangoni flow supplies liquid from the macrolayer to the three-phase contact line, it also promotes local dryout of the microlayer, which leads to a CHF reduction. It was reported that SRFs promote a more rapid detachment of smaller bubbles at lower superheats and shorten bubble waiting periods, which induces stronger turbulence and intensifies heat flux [42][43][44].…”
Section: Self-rewetting Fluidsmentioning
confidence: 99%
“…Sahu et al [43] studied the boiling of Novec 7300 and 1-heptanol-based SRF on a copper surface covered with coppercoated nanofibers and found that the simultaneous use of an SRF and a modified surface provides even better performance than either of the enhancement techniques on their own, although the enhancement was significant only at a very high heat flux. Hu et al [42] evaluated the boiling of a 1-heptanol-based SRF on a titanium dioxide coated surface and found that both the CHF and HTC can be significantly enhanced using the SRF. Furthermore, a significant reduction in the bubble diameter was observed.…”
Section: Boiling Of Srfs On Modified Surfacesmentioning
confidence: 99%
“…Coatings 2022, 12, 296 2 of 23 Animasaun et al [10] demonstrated that growth in the values of the Casson parameter causes velocity curve augmentation and temperature curve reduction. EL-Kabeir et al [11] investigated the effect of chemical reactions on the mixed convection flow of Casson liquid over a sphere.…”
Section: Introductionmentioning
confidence: 99%
“…Among them are included the ultrafine particles of zinc, aluminum, and titanium oxides (ZnO, Al 2 O 3 , TiO 2 ). They were investigated experimentally in a variety of energy systems, including heat exchangers, cooling, pool boiling, and transformer systems [20][21][22][23][24][25][26], in addition to extensive numerical simulation studies demonstrating the efficacy of these oxides in promoting heat transfer [27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%